การวิจัยและพัฒนาเทคนิคการออกแบบแบบสอบถามอิเล็กทรอนิกส์เพื่อเพิ่มความเต็มใจในการตอบและอัตราการตอบกลับ - สุรศักดิ์ เก้าเอี้ยน (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
The research objectives were 1) to study techniques for designing e-questionnaires that were used in research and constructing a general e-questionnaire by using the techniques from e-questionnaire synthesis 2) to develop techniques for designing e-questionnaires to increase willingness to respond and response rate 3) to compare the willingness to respond and response rate between the general e-questionnaire and the developed e-questionnaire. The research and development employed a mixed-method model between the quantitative research and qualitative research by collecting data with an interviewing, brainstorming and experiment. The survey samples were 30 students majoring in and faculty members of Department of Educational Research and Psychology, and the experimental study samples consisted of students and teachers in the schools in Bangkok. The research instruments were an e-questionnaire checklist, the brainstorm guideline, a general e-questionnaire and a developed e-questionnaire. The data analysis covered content analysis, descriptive statistic, conjoint analysis and chi-square test. The research findings were: 1. Techniques for designing an e-questionnaire that were the results of an synthesis of e-questionnaires used in research were having a preface in the first page, designing e-questionnaires in a long form, using the HTML interface, changing pages by scrolling, using no color background and no any graphics, using the default font type, and 12-16 pt and black text. These techniques were used to construct a general e-questionnaire. 2. The developed e-questionnaire was constructed by using the techniques for designing e-questionnaires that were the result of the conjoint analysis consisted of having a preface in the first page, designing e-questionnaire in a short form, using the Flash animation interface, changing pages by scrolling and linking, using a color background and insert graphics, using the default font type, 16 pt and colored text. 3. The results of experimental study to compare willingness to respond and response rate between a general e-questionnaire and developed e-questionnaire were: the developed e-questionnaire received both willingness to respond and response rate more significantly than the general e-questionnaire. 4. The results of brainstorming to develop techniques for designing e-questionnaires to increase willingness to respond and response rate were: an e-questionnaire that can increase willingness to respond and response rate was constructed by having a preface in the first page, designing in a short form, using HTML or Flash animation interface depending on the suitable content of the questionnaire, changing pages by scrolling and linking, using a color background and insert graphics, using the default font type colored text that can change text size as required.